PEGylated anticancer-carbon nanotubes complex targeting mitochondria of lung cancer cells - Kim, Sang-Woo; Kyung Lee, Yeon; Yeon Lee, Jong; Hee Hong, Jeong; Khang, Dongwoo (Nanotechnology, 2017)
Although activating apoptosis in cancer cells by targeting the mitochondria is an effective strategy for cancer therapy, insufficient targeting of the mitochondria in cancer cells restricts the availability in clinical treatment. Here, we report on a polyethylene glycol-coated carbon nanotube (CNT)-ABT737 nanodrug that improves the mitochondrial targeting of lung cancer cells. The polyethylene glycol-coated CNT-ABT737 nanodrug internalized into the early endosomes via macropinocytosis and clathrin-mediated endocytosis in advance of early endosomal escape and delivered into the mitochondria. Cytosol release of the nanodrug led to apoptosis of lung cancer cells by abruption of the mitochondrial membrane potential, inducing Bcl-2-mediated apoptosis and generating intracellular reactive oxygen species. As such, this study provides an effective strategy for increasing the anti-lung cancer efficacy by increasing mitochondria accumulation rate of cytosol released anticancer nanodrugs.